PEMANFAATAN BOTTOM ASH PEMBAKARAN PLTSA SEBAGAI SUBSITUSI PASIR PENYUSUN PAVING BLOCK - Krisdiansyah, Gilang; Simanihuruk, Bertinus; Handika, Nuraziz; Dewanti, Dian Purwita; Mutiara, Ayudia (Politeknik Negeri Jakarta, 2024)
Waste management in Indonesia poses a significant challenge, and to address this issue, the government has established waste-to-energy plants (Pembangkit Listrik Tenaga Sampah - PLTSa) in Bantar Gebang that generate bottom ash waste. This study focuses on utilizing bottom ash as a substitute for fine aggregate in the production of concrete paving blocks. The research aims to analyze the compressive strength, abrasion, and absorption properties of the paving blocks with various mixtures of bottom ash (0%, 10%, 30%, 50%, 60%, 80%, and 100%) at a curing age of 28 days. The results indicate that the use of bottom ash as a substitute for fine aggregate increases the compressive strength of the paving blocks. The mixture with 100% bottom ash exhibits the highest compressive strength due to the high content of calcium oxide and silicon dioxide, similar to cement content. However, the replacement of up to 50% of fine aggregate with bottom ash leads to an increase in abrasion values, indicating reduced abrasion resistance. On the other hand, paving mixtures containing 60% to 100% bottom ash show improved abrasion resistance compared to lower percentages. Absorption tests reveal that mixtures containing 10% to 100% bottom ash exhibit higher absorption values compared to the control sample without bottom ash, attributed to the high absorption capacity of bottom ash compared to sand. In conclusion, this study highlights that bottom ash from PLTSa can be effectively used as a substitute material in the production of paving blocks, leading to enhanced compressive strength and abrasion resistance. However, careful consideration of the percentage of substitution is essential to ensure compliance with the quality standards. This innovative approach has the potential to contribute to the reduction of negative impacts from PLTSa waste and offer a sustainable solution to waste management in Indonesia, promoting environmental conservation and improving infrastructure quality in the long run.